Towards the Prediction of Antimicrobial Efficacy for Hydrogen Bonded, Self‐Associating Amphiphiles. (16th October 2020) - Allen, Nyasha; White, Lisa J.; Boles, Jessica E.; Williams, George T.; Chu, Dominique F.; Ellaby, Rebecca J.; Shepherd, Helena J.; Ng, Kendrick K. L.; Blackholly, Laura R.; Wilson, Ben; Mulvihill, Daniel P.; Hiscock, Jennifer R.
Abstract: Herein we report 50 structurally related supramolecular self‐associating amphiphilic (SSA) salts and related compounds. These SSAs are shown to act as antimicrobial agents, active against model Gram‐positive (methicillin‐resistant Staphylococcus aureus ) and/or Gram‐negative ( Escherichia coli ) bacteria of clinical interest. Through a combination of solution‐state, gas‐phase, solid‐state and in silico measurements, we determine 14 different physicochemical parameters for each of these 50 structurally related compounds. These parameter sets are then used to identify molecular structure‐physicochemical property‐antimicrobial activity relationships for our model Gram‐negative and Gram‐positive bacteria, while simultaneously providing insight towards the elucidation of SSA mode of antimicrobial action. Abstract : The antimicrobial efficacy of 50 supramolecular self‐associating salts (SSAs) and related compounds was established against MRSA and E. coli . In addition, 14 different physicochemical properties were determined experimentally for each compound within this library. From these data we identified relationships between compound structure, physiochemical property, and antimicrobial activity.